Saving all the pieces: An inadequate conservation strategy for an endangered amphibian in an urbanizing area. (October 2021) - Stokes, David L.; Messerman, Arianne F.; Cook, David G.; Stemle, Leyna R.; Meisler, Julian A.; Searcy, Christopher A.
Abstract: Species conservation often focuses on preserving populations on remnant habitat patches, typically without evidence that this approach is sufficient for halting declines. We employed a 19-year dataset to examine the adequacy of this approach for recovering the Sonoma County distinct population segment of California tiger salamanders (SCTS; Ambystoma californiense ), California, USA, which now exists almost entirely in remnant habitat patches designated as preserves across a rapidly urbanizing landscape. We estimated relative SCTS larval densities from standardized annual surveys from 2002 to 2020 across 118 vernal pools in eight preserves. We found that relative larval SCTS densities decreased by 48% over the study period, indicating that current efforts to conserve SCTS are inadequate for long-term viability. Increased densities were only observed at the single study preserve where SCTS were introduced. Temporal trends in larval density among preserves were best explained by the number of pools available to SCTS, and the ability of breeding pools to retain water throughout the larval period. Specifically, preserves with >1 breeding pool and ≥1 breeding pool that held water for at least two months following the breeding season (into late April) even in dry years had substantially lower rates of larval decline. Active conservation management of preserves, including provision of multiple breeding pools, at least some of which are resilient to variable future precipitation regimes, will be required to effectively conserve SCTS. We expect these findings to apply broadly to the conservation of many species of pool-breeding amphibians.